Web Application as a Link Organizer for Educators, Staffs, and Students - Lianly Rompis; Aditya Lapu Kalua (Soegijapranata Catholic University, 2022)
Current digital transformation encourages the improvement of online learning process development through the internet networks with social media platforms, learning applications, and websites. The evolution of creativities and innovations in various fields support the creation of various new learning applications that must be known and used by educators, staffs, and students in a university. In addition, online webinars and online learnings have also started to become a new routine or daily activity in the world of education. Every learning application, online webinar, online learning, and other online media generally has a special link where each user must at least remember, record, save, or search for the link through search engines or copy from email or social media chat so that at any time they can access it. The problem is that sometimes due to busy work and age, we often forget to remember these links. Sometimes we remember and record it, but need more time to type it in its long sentence or URL. There are even special links that cannot be searched using the search engines Google, Yahoo, and so on. This will certainly be an obstacle and quite a hassle for educators and education staff, especially if the links that must be accessed are very large, tens or even hundreds of them. This research provides a solution to the above problems by designing a web application that functions as a link organizer that makes it easier for educators, staffs, and students to store learning application links and other important links so that when needed, they just open the web and click the link. which has been saved. This study method such as observation, system design, interface design, application design, and testing of a web application as a link organizer. The results provide positive future works that can be further developed and refined.